Effect of Agency Costs on Executive Compensation in South African Commercial Banks - Olarewaju, Odunayo Magret; Migiro, Stephen Oseko; Sibanda, Mabutho (Journal of Economics and Behavioral Studies, 2017)
This study examines the roles of agency cost (monitoring and bonding cost) on compensation of managers with a view from the managerial-power approach to agency cost. We modelled managers’ compensation and agency cost of banks to emphasise the potential influence of agency cost on managers’ compensation. A Panel Generalised Least Square model was estimated on four largely-controlled commercial banks in South Africa over the period 2010-2015. The result shows that shareholders’ fund, management share option, monitoring and bonding cost were strongly significant in explaining the managers’ compensation in the banks. Therefore, in the South African banking sector, compensation of managers should be based on their managerial power and not only on the principle of optimal-contracting. It is recommended, among others, that monitoring and bonding costs in the South African banks should be re-emphasised and strictly committed to. This should be so because there are direct effects of these costs on managers’ compensation which might be the reason for the persistent agency problem in the banks.